MANAJEMEN LABA PADA BANK SYARIAH DI INDONESIA: PERAN KOMITE AUDIT DAN DEWAN PENGAWAS SYARIAH - Suryanto, Tulus (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2014)
This study examined the role of the audit committee and the shariÃ¢â‚¬â„¢ah supervisory board on earnings management in islamic banks in Indonesia. Research on islamic banking industry in Indonesia. The data used in this study were derived from secondary data that is derived from the quarterly reports of banking in the year 2010Ã‚Â to 2012. This study is an empirical test using secondary data. Results of the study confirms the two hypotheses were examined: the size of the audit committee in preventing acts earnings management in islamic banks significant positive effect. this is attested by p value 0.008; 2; The size of the shariÃ¢â‚¬â„¢ah supervisory board was not able to reduce the amount of earnings management in islamic banks. Based on the results of hypothesis testing found that the variable sharia supervisory board has no effect. This may be due to the shariÃ¢â‚¬â„¢ah supervisory board to meet the regulations of Bank Indonesia only. Keywords: audit committee, shariÃ¢â‚¬â„¢ah supervisory board and management profit